2010
DOI: 10.5713/ajas.2010.10124
|View full text |Cite
|
Sign up to set email alerts
|

Garlic (Allium sativum) Supplementation: Influence on Egg Production, Quality, and Yolk Cholesterol Level in Layer Hens

Abstract: Forty-eight 40-wk-old Hi-sex laying hens were individually caged in an environmentally controlled house to evaluate the effect of garlic (Allium Sativum) juice administration on egg production, egg quality, and yolk cholesterol. Garlic juice was prepared by blending pealed garlic cloves with distilled water (1:1, w/w). Hens were randomly divided into four equal groups; one served as a control and the other three groups were individually gavaged, 3.75 ml, 7.5 ml, or 15 ml garlic juice, three times a week, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 40 publications
9
35
3
5
Order By: Relevance
“…There were not substantial differences with regard to the total cholesterol content of egg yolk regardless of the findings of other researchers demonstrating that the serum and the egg yolk cholesterol concentrations decreased (P<0.05) with increasing levels of dietary garlic (Chowdhury et al, 2002, Khan et al 2008Połtowicz and Węśyk, 2006;Canogulari et al, 2010). Our results agreed with those of Mahmoud et al (2006), who observed that the addition of garlic juice at 0.25, 0.50 and 1% did not change (P>0.05) yolk cholesterol concentration. In our opinion, this could be attributed to the relatively constant amount of cholesterol in egg yolk, needed for the normal embryonic development, i.e.…”
Section: Lipid and Fatty Acid Content Of Egg Yolksupporting
confidence: 83%
“…There were not substantial differences with regard to the total cholesterol content of egg yolk regardless of the findings of other researchers demonstrating that the serum and the egg yolk cholesterol concentrations decreased (P<0.05) with increasing levels of dietary garlic (Chowdhury et al, 2002, Khan et al 2008Połtowicz and Węśyk, 2006;Canogulari et al, 2010). Our results agreed with those of Mahmoud et al (2006), who observed that the addition of garlic juice at 0.25, 0.50 and 1% did not change (P>0.05) yolk cholesterol concentration. In our opinion, this could be attributed to the relatively constant amount of cholesterol in egg yolk, needed for the normal embryonic development, i.e.…”
Section: Lipid and Fatty Acid Content Of Egg Yolksupporting
confidence: 83%
“…However, these results are different from the findings reported by Sakine and Onbasilar (2006) who observed that the supplementation of garlic powder had no significant effect on egg breaking strength, shell thickness, albumen index, yolk index and HU. Mahmoud et al (2010) observed that garlic juice supplementation improved albumen height and HU in the 40-week-old Hi-sex laying hen. Kaya and Macit (2012) found that supplementation of dried garlic powder had no positive effect on egg shell thickness and HU in the laying hen.…”
Section: Egg Qualitymentioning
confidence: 99%
“…Certain feed additives showed promise, such as beta-cyclodextrin (Sparks, 2006), inulin (Shang et al, 2010), 0.5% multispecies probiotics (Khan et al, 2011), antioxidant, vitamins E or C (Mohiti-Asli & Zaghari, 2010, combinations of garlic and black tea (2%) (Azeke & Ekpo, 2009), 0.5% ginger root powder (Akbarian et al, 2011), up to 3.0% Nigella sativa (Islam et al, 2011) and pumpkin seeds (Celik et al, 2011). No effects on the total cholesterol content of eggs occurred when layer diets were supplemented with aromatic herb oils (thyme, sage or rosemary) (Bolukbasi et al, 2008), dried purslane (Aydin & Dogan, 2010), garlic juice (Mahmoud et al, 2010) and plant sterols (Liu et al, 2010). Other reports showed that certain feed ingredients, such as lysolecithin could increase the cholesterol content of yolk (Han et al, 2010).…”
Section: Introductionmentioning
confidence: 99%